Financial performance of small enterprises: a university experience - Wong, David (1995)
The Pacific University's Management Training Program (PEG), the aim of which is the creation of small businesses, has been implemented for nine years. This article is an attempt to describe and analyze various aspects of these companies' financial activities during the program's first six years (1986-1991). The article examines aspect to do with finance, liquidity and profitability in the businesses that have been set up, along with any direction changes they may have taken and how many are still operating. Finally a number of recommendations are made for improving the financial assessment of PEG businesses.